DIGITAL ANALYTICS AS A FACTOR IMPROVING THE QUALITY OF HIGHER EDUCATION - Akhmetov, Б.С.; Oshanova, Н.Т.; Akhmetov, Б.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article examines the global and domestic experience of the impact of digital analytics on the quality of higher education. The importance and relevance of the planned research lies in its potential to improve the quality of higher education and adapt to modern challenges. The use of digital analytics in education makes it possible to identify important factors influencing student success, the effectiveness of educational programs and learning processes. One of the key challenges facing higher education is the processing and analysis of large amounts of data generated in higher education institutions. Information about students, curricula, teachers and learning processes is continuously accumulated in education management systems. The analysis of this data using digital analytics makes it possible to identify patterns, trends and important factors affecting the quality of education. However, the development and application of innovative methods and tools for efficient processing and analysis of such a volume of information is required.